Determinants Affecting Small Business Financially in Nepal: A Structural Equation Modelling Analysis - Shakya, Bimal; Karki, Dipendra; Prajuli, Seeprata; Bhandari, Udbodh; Kayestha, Mijala (Quest Journal of Management and Social Sciences, 2024)
Background: Small businesses in Kathmandu Valley play a crucial role in local economies by creating jobs, fostering community connections, and driving growth and innovation. However, they face significant financial challenges that can hinder their development. Objective: This study aims to analyze the determinants that affect small businesses financially in Kathmandu Valley, focusing on how these factors influence business growth and sustainability. Method: An exploratory research design was employed, with data collected through structured questionnaires. Structural Equation Modeling (SEM) was used for inferential analysis. The study sampled 403 individuals from the Kathmandu Valley to represent the population. Result: The SEM analysis identified four constructs as fitting well with the model out of six. The results reveal that globalization and external factor risk significantly impact financial hurdles faced by small businesses. Additionally, government policy was found to play a moderating role, partially mediating the relationship between the dependent and independent variables and showing a significant impact. Conclusion: The study highlights key determinants that affect the financial aspects of small businesses in Kathmandu Valley. By identifying these factors, the research provides insights into how small enterprises can be better supported financially, contributing to their growth and long-term sustainability. Paper Types: Research Paper Keywords: Financial Hurdles, Small Business, Structural Equation Modeling, Financial Management JEL Classification: M00, F65, G28, E44 and C50